Das Pampaproblem in vergleichend ökologischer Betrachtung und seine Lösung - Walter, Heinrich (ERDKUNDE, 1967)
1. The problem of the Pampa arose because it was believed that the climate of the Pampa area is humid. Theoretical reflections appeared to verify this. 2. Accurate observations in the field however, show that there are very many lagoons i.e. shallow lakes and pools, which have no outflow. 3. The water in these basins has very high pH values, of 8 and over, culminating in soda (Na2COs) formation. Solonets-type soda soils with Distichlis and other characteristic types are also very widespread in the level lands of the pampa deprimada and the pampa alta. 4. The facts given in 2. and 3. are not compatible with an allegedly humid climate and indeed indicate that potential evaporation must exceed mean annual precipitation. 5. Values of mean potential evaporation (Tank type A) for the province of Buenos Aires made available by the Servicio Meteorologico Nacional clearly show that with the possible exception of the La Plata shore zone, the water balance in the whole of the Pampa area is negative. The Pampa area has a climate similar to a weak semiarid type in which, as is the case in the forest steppe of East Europe, aridity increases from NE to SW. 6. The boundary line between grassland and forest/ woodland is not directly determined by climate or soil. The decisive factors are the competitive ability of grass land types on the one hand and tree types on the other. From the standpoint of latitude and climate, the Pampa is most easily comparable with the Prairie in Oklahoma USA. The climatic diagram of Buenos Aires is reminiscent of Oklahoma City. 7. The original Pampa vegetation was formed by grass land associations, which in the NE were very species-rich, becoming poorer towards the SW. It is not necessary to assume that lack of trees can be traced back to human activity (burning) in pre-Columbian times. The Indians settled primarily the coastal area in the La Plata and it is just here that the most numerous woodland remnants are found. As they possessed no horses, their hunting areas were limited to the coastal zone. The treeless ness of the Pampa must be explainable on a natural basis. 8. It is false to assume that grasslands always occur in a more arid climate than woodland. The latter are found in a drier climate on the dry boundary of the Pampa, there where the provinces of Buenos Aires and La Pampa meet. With precipitation declining further from 500 mm to 200 mm in the hot arid areas, a vegetation succession on sandy soils begins, like that found in SW Africa. The woodland fades into a tree savanna, then into shrubland and lastly into a bush savanna.